Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content 1. The Degree to which Arabic Language Teachers in Saudi Arabia Possess Distance Learning Competencies Misfer Saud Mubarak Al-Hersh 2. The 21st Century Skills Included in family Education and Life Skills Course for the Secondary Stage Amani Hashim Alzubaidi, Abeer Mohammed Alarfaj 3. The Degree of Availability of the Science, Technology, Society and Environment (STSE) approach in science curricula in the Sultanate of Oman Humood Sulieman Saif Al-Rumhi, Ahmed Humaid Mohammed Al-Badri 4. Using Inquiry Strategy in Teaching Social Studies to Develop Metacognitive Studies among Second Grade Intermediate Students Noier Hamdan Alghedani 5. The effectiveness of using simulation strategy in developing Arabic calligraphy skills for eighth grade students in the Capital Municipality Abdulkareem Ali Mohamed Al-Lahabi 6. The Reality of Continuous Evaluation in the English Language Course in the Elementary Stage in Saudi Arabia Mishal Abdullah Algosairi, Ahmad Hasan Albdour 7. Constructing an instrument to measure attitude towards distance learning and applying it to a sample of the students of Mu’tah University Nofah Sameh Kamel Al-Mawadeh, Hanin Lafi Zal Al-Mawadeh